Etika vs Estetika dalam Dakwah: Studi Etnografi Virtual pada Akun Instagram @nunuzoo - Muh. Yahya Saraka; Topikurohman Topikurohman; Nadya Shabrina (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2026)
This study analyzes meaning construction in humorous da'wah videos prohibiting dating on Instagram @nunuzoo through Barthesian semiotics, and examines the negotiation between ethical and aesthetic dimensions in digital da'wah content. Using a qualitative virtual ethnography approach, data were collected from five purposefully selected videos through online participant observation, in-depth interviews, and digital artifact documentation. Analysis employed the four-level Cyber Media Analysis and Barthesian semiotics. Denotatively, all videos depicted literal rejection of dating proposals; connotatively, rejection was associated with religious understanding; mythically, the belief was naturalized that dating leads to fornication and marriage is the sole divinely approved alternative. This myth entails problematic simplification that neglects premarital readiness and arguably resonates with the logic driving high marriage dispensation rates. All da'wah messages were moral (akhlak), with humor employing incongruity and degradation. The dominant interaction was comment-to-tag (71.71%), forming a "digital word-of-mouth da'wah" mechanism. The ethics-aesthetics dialectic manifested in a content shift from humor-da'wah to da'wah-humor. This study offers an integrative model of semiotics and virtual ethnography for digital da'wah research. Identifying comment-to-tag as a religious message distribution mechanism and analyzing the ethics-aesthetics dialectic constitute this study's original contributions.